Macrophage pyroptosis mediates hyperoxia-induced inflammatory lung injury in neonates - Tu, Zikun; Guo, Haiyan; Gao, Yajing; Xiao, Wenfeng; Xie, Xueru; Yu, Hongmiao; Liang, Qiuyan; Zhou, Yufeng (Frontiers in Immunology, 2025)
BackgroundHyperoxia plays a key role in the development of bronchopulmonary dysplasia (BPD), a chronic lung disease of preterm infants. This study aimed to investigate the role of NLRP3/caspase-1/gasdermin D (GSDMD)-mediated pyroptosis in hyperoxia-induced lung injury in neonatal mice and to evaluate the potential protective effects of the caspase-1 inhibitor VX-765 on alveolar and vascular development in hyperoxia-exposed lungs.Materials and methodsC57/BL6 mouse pups were randomized on postnatal Day 4 (PN4) to receive daily intraperitoneal injections of VX-765, an effective and selective caspase-1 inhibitor, or a vehicle during exposure to room air or hyperoxia (85% O2) for 10 days. Alveolarization was assessed by H&E staining. Pulmonary vascular development was detected by CD31 immunohistochemistry. The degree of fibrosis was analyzed by Masson staining. TUNEL and Ki67 immunofluorescence staining was performed to assess overall cell survival in lung tissue. Concentrations of IL-1β was detected by ELISA in lung homogenates. The expressions of pyroptosis-associated proteins, NLRP3, Caspase-1 p20, N-GSDMD and mature IL-1β were evaluated by Western blot. Immunofluorescence colocalization of F4/80 with NLRP3/Caspase-1/IL-1β was performed. CD68 and AQP5 protein expression was analyzed by immunohistochemistry.ResultsHyperoxia activated the NLRP3 inflammasome, increased the production of mature IL-1β, and upregulated the expression of N-GSDMD, the active form of GSDMD that is responsible for the programmed cell death mechanism of pyroptosis in lung tissue. Importantly, VX-765 decreased NLRP3, IL-1β activation, and N-GSDMD expression and improved alveolar and vascular development by inhibiting pyroptosis of macrophages in hyperoxia-exposed lungs. Moreover, VX-765 also promoted cell proliferation and AT1 survival in the hyperoxia-exposed lung.ConclusionNLRP3/Caspase-1/GSDMD-mediated pyroptosis plays a critical role in hyperoxia-induced neonatal lung injury, and targeting this pathway may be beneficial for the prevention of lung injury in preterm infants.